Problems Of Inheritance Of Wills For The Heirs Of Ninggal Kedaton - I Putu Riko Sariwisesa; Abraham Ferry Rosando (Fakultas Hukum Dehasen, 2024)
Customary Law in terms of inheritance. The problem of inheritance disputes is very common and often occurs in people's lives. The type of research used is Normative Research with the method of collecting legal materials used in this research through literature study and the approach used in legal research is a statutory approach and a conceptual approach. The various cultural and religious backgrounds in Indonesia are the cause of differences in the distribution of inheritance in each group of society. The absence of regulations in Indonesia that specifically regulate inheritance makes the division of inheritance confusing, especially for the Balinese traditional community, most of whom are Hindu. In general, people who are not Muslim adhere to the inheritance system regulated in the Civil Code (KUHPer), however, the Balinese Hindu community has its customary law, where the position of customary law is higher than the Civil Code. However, in reality, many Balinese Hindu communities adhere to Western Civil Law, and it is not uncommon for many people to submit wills to a Notary to give away their assets to their children who have converted. In this case, giving property by will to heirs who are no longer Hindu is prohibited under Balinese Customary Law. Therefore, it is necessary to analyze decision number 834/Pdt.G/2016/PN Dps because the lawsuit was granted by the Denpasar District Court, which makes it seem as if Customary Law is lower than Western Civil law.